2020
DOI: 10.3390/cells9061381
|View full text |Cite
|
Sign up to set email alerts
|

BMP-2 Variants in Breast Epithelial to Mesenchymal Transition and Microcalcifications Origin

Abstract: This study aims to investigate the possible different roles of the BMP-2 variants, cytoplasmic and nuclear variant, in both epithelial to mesenchymal transition and in microcalcifications origin in human breast cancers. To this end, the in situ expression of cytoplasmic and nuclear BMP-2 was associated with the expression of the main epithelial to mesenchymal transition biomarkers (e-cadherin and vimentin) and molecules involved in bone metabolisms (RUNX2, RANKL, SDF-1) by immunohistochemistry. In addition, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…Our studies, amongst others, have presented robust evidence that breast cancer with microcalcifications is associated with poor clinical outcome [5,[21][22][23][24][25][26][27][28] and BMP-2 is upregulated in tissues with microcalcifications [3][4][5]. Based on the information currently available in the literature, BMP-2 is believed to be mainly secreted by cells in the tumor microenvironment, but not the breast cancer tumor cells themselves [29].…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Our studies, amongst others, have presented robust evidence that breast cancer with microcalcifications is associated with poor clinical outcome [5,[21][22][23][24][25][26][27][28] and BMP-2 is upregulated in tissues with microcalcifications [3][4][5]. Based on the information currently available in the literature, BMP-2 is believed to be mainly secreted by cells in the tumor microenvironment, but not the breast cancer tumor cells themselves [29].…”
Section: Introductionmentioning
confidence: 62%
“…Currently, bone morphogenetic proteins 2 (BMP-2) has been implicated to play a role in the formation of microcalcifications. BMPs are growth factors of the TGF-β super family and BMP-2 is a specific and key regulator of osteoblast-like cells [3][4][5]. Studies have shown that BMP-2 can induce breast cancer cells to acquire osteoblastic characteristics, leading to the formation of microcalcifications [6].…”
Section: Introductionmentioning
confidence: 99%
“…Bone morphogenetic proteins (BMPs) are important members of the TGF-β superfamily. At present, more than 20 BMPs have been discovered, and their biological functions are very extensive, including promoting bone and cartilage production, regulating cell proliferation and differentiation, and regulating the growth and development of various organs [18] , [19] , [20] , [21] , [22] , [23] . Studies have found that BMP-2 can activate Smad-independent pathways in tumor cells, including in the cancers of the breast, stomach, colon, and pancreas; for example, the PI3K/Akt signaling pathway to promote tumor cell invasion and metastasis [24] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, rhBMP-2 induces EMT in three BC cell lines (MCF-7, MDA-MB-231, and mouse BC cell line 4T1) and enhances cell migration and invasion ability both in vivo and in vitro [19 , 22] . Aberrant expression of BMP-2 has been observed in various tumors and is known to be closely related to EMT induction and tumor invasion [ [18] , [19] , [20] , 22 , 23] .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, a recent study displayed a correlation between the presence of BOLCs and the development of bone metastatic lesions within five years from histological diagnosis [ 28 , 57 ]. Li Zhang et al discovered that the tumor tissue produces BMP-2 locally through autocrine or paracrine ways, which combines with related receptors and enters the nucleus, acts at the target gene, and then regulates RUNX2, OPN, and other bone matrix proteins to form a microenvironment of calcium and phosphorus deposits in the tumor tissue, resulting in the formation of microcalcifications [ 51 ].…”
Section: Microcalcifications In Breast Cancermentioning
confidence: 99%